A rare cause of hyperamylasemia: A case with pneumothorax and subcutaneous emphysema around the parotid gland in a trauma patient - ASYA, ORHAN (My University, 2021)
Amylase is a common laboratory test in emergency departments, especially in trauma patients. Although hyperamylasemia is mostly caused by injury to the pancreas in trauma patients, non-pancreatic causes of hyperamylasemia are not rare. Being aware of these causes may prevent unnecessary diagnostic tests. In this study, we presented a trauma patient with hyperamylasemia of non-pancreatic origin. Possible mechanisms of hyperamylasemia in our case are acute hypoxia-induced hyperamylasemia because of left lung pneumothorax and massage-like activity of subcutaneous emphysema around the parotid gland.
Keywords: Hyperamylasemia; Acute pancreatitis; Pneumothorax; Subcutaneous emphysema; Parotitis